Draft Sixth Five Year Plan 1980-85 Part-II-Plan Proposals in Detail Government of the Union Territory of Goa, Daman and Diu - Planning Commission (Planning Commission, 1980)
The planned development work in the field of Agriculture was taken up in this Territory from the year 1963. To begin with, an approximate outlay of Rs.20.00 lakhs was provided annually for implementation of various agricultural programmes. This was gradually increased to Rs.50.00 lakhs per year by the end of the Fifth Plan Period.
Government of the Union Territory of Goa, Daman and Diu, Department of Planning and Statistics